Modeling of acoustic emission signals at fracture of composite materials under shear loading - Філоненко, С.Ф.; Косицька, Т.М.; Космач, О.П. (Proceedings of National Aviation University (archive), 2010)
Modeling of composite material fracture and formed of acoustic emission signal is conducted depending on physical-mechanical properties of material, and also terms of loading. Basic conformities to the law of change of acoustic emission signal parameters of are rotined at a change of loading speed and physical-mechanical properties of composite material.